LC-MS/MS-based serum proteomics reveals a distinctive signature in a rheumatoid arthritis mouse model after treatment with mesenchymal stem cells. - Namhee Jung; Soyoung Park; TaeHo Kong; Hwanhee Park; Woo Min Seo; Seunghee Lee; Kyung-Sun Kang (PLoS ONE, 2022)
Mesenchymal stem cells (MSCs) are known to be able to modulate immune responses, possess tissue-protective properties, and exhibit healing capacities with therapeutic potential for various diseases. The ability of MSCs to secrete various cytokines and growth factors provides new insights into autoimmune-diseases such as rheumatoid arthritis (RA). RA is a systemic autoimmune disease that affects the lining of synovial joints, causing stiffness, pain, inflammation, and joint erosion. In recent years, MSCs-based therapies have been widely proposed as promising therapies in the treatment of RA. However, the mechanism involved in disease-specific therapeutic effects of MSCs on RA remains unclear. To clarify the mechanism involved in effects of MSCs on RA, proteomic profiling was performed using an RA mouse model before and after treatment with MSCs. In this study, treatment efficacy of human umbilical cord blood-mesenchymal stem cells (hUCB-MSCs) was confirmed using a type II collagen-induced arthritis (CIA) mouse model. Results of measuring incidence rates of arthritis and clinical arthritis index (CAI) revealed that mice administrated with hUCB-MSCs had a significant reduction in arthritis severity. Proteins that might affect disease progression and therapeutic efficacy of hUCB-MSC were identified through LC-MS/MS analysis using serum samples. In addition, L-1000 analysis was performed for hUCB-MSC culture medium. To analysis data obtained from LC-MS/MS and L-1000, tools such as ExDEGA, MEV, and DAVID GO were used. Results showed that various factors secreted from hUCB-MSCs might play roles in therapeutic effects of MSCs on RA, with platelet activation possibly playing a pivotal role. Results of this study also suggest that SERPINE1 and THBS1 among substances secreted by hUCB-MSC might be key factors that can inhibit platelet activation. This paper is expected to improve our understanding of mechanisms involved in treatment effects of stem cells on rheumatoid arthritis.